The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/jb.186.24.8478-8489.2004
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Identification of Genes Required for Full Virulence ofStaphylococcus aureus

Abstract: Gene products required for in vivo growth and survival of microbial pathogens comprise a unique functional class and may represent new targets for antimicrobial chemotherapy, vaccine construction, or diagnostics. Although some factors governing Staphylococcus aureus pathogenicity have been identified and studied, a comprehensive genomic analysis of virulence functions will be a prerequisite for developing a global understanding of interactions between this pathogen and its human host. In this study, we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 62 publications
4
85
0
Order By: Relevance
“…CI is a sensitive measure of the relative degree of virulence attenuation of a particular mutant in mixed infections with the wild-type strain (Benton et al, 2004). To provide more data about the virulence of the mutants, CI was determined in vivo, using an established mouse subcutaneous model of infection (Horsburgh et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CI is a sensitive measure of the relative degree of virulence attenuation of a particular mutant in mixed infections with the wild-type strain (Benton et al, 2004). To provide more data about the virulence of the mutants, CI was determined in vivo, using an established mouse subcutaneous model of infection (Horsburgh et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…CI was measured as described previously (Benton et al, 2004) in an established murine abscess model of infection (Horsburgh et al, 2001), with the following modifications. Mutant and wild-type strains were separately grown to stationary phase in BHI broth, harvested, washed and resuspended in sterile PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Genome scanning has predicted 17 potential TCSs in S. aureus, some of which have been reported to be regulators of bacterial virulence. The AgrCA TCS is a well-known global regulatory system controlling numerous genes involved in S. aureus virulence, such as cytotoxin-and hemolysin-encoding genes, but other TCSs, such as ArlSR, SaeSR, VraSR, and SsrAB, have also been reported to play roles in S. aureus virulence (2,32,41).…”
mentioning
confidence: 99%
“…Microarray analysis and proteomics have revealed that most of the genes activated by sae are involved in bacterial adhesion, immune modulation, or toxicity (25,29,38). In addition, the importance of gene regulation by sae in vivo was shown in several animal models (3,15,16,29,43).The sae locus consists of four open reading frames, two of which (saeR and saeS) show strong sequence homology to response regulators and to histidine kinases (HKs) of bacterial two-component regulators (10). Two additional open reading frames, saeP and saeQ, both located upstream of saeRS, are likely to be important for the functionality of the sae operon (33, 39).…”
mentioning
confidence: 99%
“…Microarray analysis and proteomics have revealed that most of the genes activated by sae are involved in bacterial adhesion, immune modulation, or toxicity (25,29,38). In addition, the importance of gene regulation by sae in vivo was shown in several animal models (3,15,16,29,43).…”
mentioning
confidence: 99%